Children in the Streets of Koronadal City, South Cotabato, Philippines: A Situational Analysis - Quennie Marie Zuyco; Rosemary Fernandez (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study was conducted in Koronadal City, South Cotabato. It aimed to look into the current situation of street children in the city. A quantitative descriptive research design was used to determine the respondents’ profile, contributing factors that led them into the streets, challenges encountered, and suggestions and recommendations to alleviate the respondents’ situation. The data gathered was analyzed through descriptive statistics. Data revealed that demographic, health, economic, and psychosocial conditions, the experience of abuse, and awareness of child rights have an impact on the situation of the respondents of the study. The family and peers of the respondents significantly affect their behavior and are considered to be the contributing factors that pushed them to the streets. There are also health issues among the respondents; they may be at greater risk of sexual and other violence and exploitation. Some of the respondents were harmed by adults, other children, and even their own families.